System-wide approaches to uncover Th2 cell lineage commitment - Lönnberg, Tapio (Annales Universitatis Turkuensis D 1040, 2012)
T helper (Th) cells are vital regulators of the adaptive immune system. When activated by presentation of cognate antigen, Th cells demonstrate capacity to differentiate into functionally distinct effector cell subsets. The Th2 subset is required for protection against extracellular parasites, such as helminths, but is also closely linked to pathogenesis of asthma and allergies. The intracellular molecular signal transduction pathways regulating T helper cell subset differentiation are still incompletely known. Moreover, great majority of studies regarding Th2 differentiation have been conducted with mice models, while studies with human cells have been fewer in comparison. The goal of this thesis was to characterize molecular mechanisms promoting the development of Th2 phenotype, focusing specifically on human umbilical cord blood T cells as an experimental model. These primary cells, activated and differentiated to Th2 cells in vitro, were investigated by complementary system-wide approaches, targeting levels of mRNA, proteins, and lipid molecules. Specifically, the results indicated IL4-regulated recruitment of nuclear protein, and described novel components of the Th2-promoting STAT6 enhanceosome complex. Furthermore, the development of the activated effector cell phenotype was found to correlate with remodeling of the cellular lipidome. These findings will hopefully advance the understanding of human Th2 cell lineage commitment and development of Th2-associated disease states.